Teaching students with special needs in inclusive settings - Smith, Tom E.; Polloway, Edward A.; Patton, James R.; Dowdy, Carol A. (India : Pearson, 2015)
This highly praised text takes a categorical approach to covering the opportunities and challenges in creating inclusive classrooms for all students. IEP coverage, new material on Response to Intervention, chapters on both elementary and secondary classrooms as well as new features on differentiating instruction in both elementary and secondary classrooms provide the most coverage in the field of the instructional processes general education teachers will need to know.
Includes bibliographical references and indexes.
Keywords: Inclusive education -- United States; Children with disabilities -- Education -- United States; Special education -- United States; Classroom management -- United States